DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Kohorova Mohichehra; Jalolova Muqaddas (TADQIQOTLAR, 2025)
Annotation: This article explores the complex challenges teachers face when teaching foreign languages to young learners. It focuses on key issues such as cognitive limitations, emotional sensitivity, overuse of the native language, individual differences in learning styles, and limited exposure outside the classroom. The article emphasizes the importance of using age-appropriate, culturally relevant materials and fostering a supportive learning environment. It also discusses the role of parents and how their expectations can impact the learning process. Practical suggestions are provided to help teachers create more effective and engaging lessons for young language learners.